The Leishmania Surface Protease GP63 Cleaves Multiple Intracellular Proteins and Actively Participates in p38 Mitogen-activated Protein Kinase Inactivation - Hallé, Maxime (American Society for Biochemistry and Molecular Biology, 2009)
The Leishmania parasite is a widespread disease threat in tropical areas, causing symptoms ranging from skin lesions to death. Leishmania parasites typically invade macrophages but are also capable of infecting fibroblasts, which may serve as a reservoir for recurrent infection. Invasion by intracellular pathogens often involves exploitation of the host cell cytoskeletal and signaling machinery. Here we have observed a dramatic rearrangement of the actin cytoskeleton and marked modifications in the profile of protein tyrosine phosphorylation in fibroblasts infected with Leishmania major. Correspondingly, exposure to L. major resulted in degradation of the phosphorylated adaptor protein p130Cas and the protein-tyrosine phosphatase-PEST. Cellular and in vitro assays using pharmacological protease inhibitors, recombinant enzyme, and genetically modified strains of L. major identified the parasite protease GP63 as the principal catalyst of proteolysis during infection. A number of additional signaling proteins were screened for degradation during L. major infection as follows: a small subset was cleaved, including cortactin, T-cell protein-tyrosine phosphatase, and caspase-3, but the majority remained unaffected. Protein degradation occurred in cells incubated with Leishmania extracts in the absence of intact parasites, suggesting a mechanism permitting transfer of functional GP63 into the intracellular space. Finally, we evaluated the impact of Leishmania on MAPK signaling; unlike p44/42 and JNK, p38 was inactivated upon infection in a GP63- and protein degradation-dependent manner, which likely involves cleavage of the upstream adaptor TAB1. Our results establish that GP63 plays a central role in a number of hostcell molecular events that likely contribute to the infectivity of Leishmania.